Monitoring and analyzing tree diversity using i-Tree eco to strengthen urban forest management (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Mosyaftiani A, Wahyu A, Kaswanto, Wiyoga H, Syasita N, Septa AF, Djauhari D. 2022. Monitoring and analyzing tree diversity using i-Tree eco to strengthen urban forest management. Biodiversitas 23: 4033-4039. Inadequate data on vegetation growth makes it difficult for managers to determine the additional measures necessary for effective urban forest management. The management of urban forests in Jakarta also raises this issue. Collaborative research with multiple stakeholders was conducted in five Jakarta urban forests to assess the diversity and structure of the vegetation as a basis for long-term monitoring and management. Using 49 plots, we carried out a field inventory to gather information on tree number, diameter at breast height, tree height, and crown size. The i-Tree Eco programme was used to examine the data and information gathered. The widely used i-Tree Eco analysis was conducted to make viable evidence-based evaluation feasible and to help stakeholders with data processing. The results showed that the five urban forests had a moderate level of diversity, with an index value ranging from 2.1 to 3.0. The five most common tree species—Swietenia macrophylla, Terminalia sp., Delonix regia, Ceiba pentandra, and Aleurites moluccanus—dominate urban forests, whereas three of them are exotic and most native species have substantially lower values. Increasing tree diversity by enriching native species is recommended to be a top priority for urban forest management in Jakarta. Additionally, this research shows that adopting advanced and user-friendly tools to regularly monitor and analyze vegetation helps stakeholders achieve better urban forest management.